Fluid shear stress modulates endothelial cell invasion into three-dimensional collagen matrices - Kang, Hojin (Am J Physiol Heart Circ Physiol, 2008)
Endothelial cells are subjected to biochemical and mechanical stimuli, which regulate their angiogenic potential. We determined the synergistic effects of sphingosine-1-phosphate (S1P) and fluid wall shear stress (WSS) on a previously established model of human umbilical vein endothelial cell invasion into three-dimensional collagen matrices. Collagen matrices were incorporated into a parallel-plate flow chamber to apply controlled WSS to the surface of endothelial monolayers over a period of 24 h. Cell invasion required the presence of S1P, with the effects of S1P being enhanced by shear stress to an extent comparable with S1P combined with angiogenic growth factor stimulation. The number of invading cells depended on the magnitude of shear stress, with a maximal induction at a shear stress of ∼5 dyn/cm(2), whereas the invasion distance was proportional to the magnitude of shear stress. The enhancement of invasion by 5.3 dyn/cm(2) shear stress coincided with elevated phosphorylation of Akt and matrix metalloproteinase (MMP)-2 activation. Furthermore, invasion induced by the combined application of WSS and S1P was attenuated by inhibitors of MMPs (GM6001) and the phosphatidylinositol 3-kinase/Akt signaling pathway (wortmannin). These results provide evidence that shear stress is a positive modulator of S1P-induced endothelial cell invasion into collagen matrices through enhanced Akt and MMP-2 activation.